Videoactivism and new urban movements in Spain (Andamios, Revista de Investigación Social, 2015)
The article departs from political economy in order to engage critically with the role currently played by communication and culture in wider neoliberal processes of territorial redefinition and urban marketing. The text addresses recent videoactivism practices within new urban movements in Spain during the last few years as a response to such processes, foregrounding the tensions that pervade spaces of cultural resistance where conflict, difference and contradiction are still, nonetheless, possible. Our analysis attempts to make sense of interaction patterns between new forms of citizenship and the appropriation of public space through elements of self-organization seeking to reconnect with more complex patterns of urban sociability still at play in our cities.
Keywords: Videoactivism; urban marketing; democracy; social movements; cognitive capitalism